Comparison of Clinical Features in HLA-B27 Positive and Negative Patients With Axial Spondyloarthritis: Results From a Cohort of 4,131 Patients - Zhang, Shangzhu; Wang, Yanhong; Peng, Linyi; Su, Jinmei; Zeng, Xiaofeng; Li, Mengtao; Wu, Zhenbiao; Xu, Jian; Yang, Min; Wu, Lijun; Zhao, Cheng; Duan, Xinwang; et al. (Frontiers in Medicine, 2020)
Objective: The aim of our study was to assess the influence of the HLA-B27 status on axial SpA in the largest cohort in China. Methods: An observational, cross-sectional, and descriptive study of SpA patients from the China SpA database was performed. Demographic and clinical data were compared in terms of the HLA-B27 status. Univariate and multivariate analyses were performed to identify variables related to HLA-B27 presence. Results: We enrolled 4131 patients in this study; of those, 3695 (89.4%) were HLA-B27 positive. Patients with positive HLA-B27 showed a greater prevalence of male sex, family history and uveitis and a lower prevalence of psoriasis than patients with negative HLA-B27. Moreover, HLA-B27-positive patients expressed a higher disease activity measured by ASDAS-CRP, and showed a greater prevalence with the treatment of biologics than HLA-B27-negative patients. In the multivariate analysis, male gender (p＜0.001), younger age (p＜0.001), a disease duration of more than 3 years, a family history (p＜0.001), uveitis (p＜0.001), ASDAS-CRP (p＜0.001), and biologic treatment (p＜0.001) were the main variables that were independently related to HLA-B27 presence, whereas a diagnosis delay time > 36 months (p＜0.001) and psoriasis (p＜0.001) were independently related to HLA-B27 absence. Conclusion: In Chinese axial SpA patients, presence of HLA-B27 is associated with the male sex, younger age, longer disease duration, greater family aggregation and higher frequency of uveitis; absence of HLA-B27 is associated with longer diagnosis delay time and higher frequency of psoriasis.